Insertion reactions of dicyclohexylcarbodiimide with aminoboranes, -boryls and -borylenes. - Pierce, G; Coombs, N; Willock, D; Day, J; Stasch, A; Aldridge, S (2007)
Insertion reactions of dicyclohexylcarbodiimide with aminoboranes and with aminoboryl and -borylene transition metal complexes have been examined as potential routes to new boron-containing ligand systems. Reactions with systems containing two-coordinate boron centres are found to be significantly more facile than those with three-coordinate substrates. Thus, reaction of (dicyclohexylamino)boron dichloride () with dicyclohexylcarbodiimide over 36 h at 50 degrees C generates the (structurally authenticated) guanidinate complex Cy(2)NC(NCy)(2)BCl(2) () via insertion into the BN bond. By contrast, the corresponding reaction with the cationic aminoborylene complex [CpFe(CO)(2)(BNCy(2))](+)[BAr(f)(4)](-) () proceeds rapidly at ca.-30 degrees C, via initial insertion into the FeB bond to give [CpFe(CO)(2)C(NCy)(2)BNCy(2)](+)[BAr(f)(4)](-) (). Consistent with related studies, a key factor in facilitating such insertion chemistry is thought to be the formation of an initial donor/acceptor complex between the diimide and the group 13 centre. Thus, DFT studies suggest that [CpFe(CO)(2)B(NCy(2))(CyNCNCy)](+)[BAr(f)(4)](-) is a potential intermediate in the reaction of with CyNCNCy, and that further reaction to give the observed product, , is strongly exergic (-183 kJ mol(-1)). By contrast, DFT calculations for the alternative isomer [CpFe(CO)(2)B(CyN)(2)CNCy(2)](+)[BAr(f)(4)](-) (), formed by BN insertion, suggest that it is 112 kJ mol(-1) less stable than . Such experimental and computational findings imply that under reaction conditions where a suitable isomerisation pathway is available, cationic complexes such as , which contain a four-membered boron-donor heterocycle are likely to be disfavoured with respect to alternative C-bound isomers.